Simultaneous absolute protein quantification of seven cytochrome P450 isoforms in rat liver microsomes by LC-MS/MS-based isotope internal standard method - Jiang, Fulin; Zhang, Chang; Lu, Zihan; Liu, Jingyu; Liu, Peiqing; Huang, Min; Zhong, Guoping (Frontiers in Pharmacology, 2022)
The cytochrome P450 (CYP) enzymes play a pivotal role in drug metabolism. LC-MS/MS-based targeting technology has been applied to the analysis of CYP enzymes, promoting drug development and drug-drug interaction studies. Rat is one of the most commonly used models for drug metabolism assessment, but LC-MS/MS assay quantifying the abundance of CYP enzymes in rats is rarely reported. Herein, an accurate and stable LC-MS/MS based method was developed and validated for the simultaneous quantification of seven major rat CYP isoforms (CYP1A2, 2B1, 2C6, 2C11, 2D1, 2E1 and 3A1) in liver microsomes. The careful optimization of trypsin digestion and chromatography combined with isotope-labeled peptide as internal standard improved the efficiency and accuracy of the analysis. Highly specific surrogate peptides were obtained by a procedure including trypsin digestion for six hours and separated on a Hypersil Gold C18 column (100 x 2.1 mm, 3 μm) using gradient elution for 15 min with a mobile phase of water containing 0.1% formic acid and acetonitrile. In the method validation, linearity, matrix effect, recovery, stability, accuracy, and precision all meet the requirements. Subsequently, this method was applied to detect seven enzymes in rat liver microsomes from four different sources, and the correlation between the abundance and activity of CYP enzymes was further analyzed. The high-throughput detection method provided in this study will provide support for pertinent pharmaceutical research based on rat models.